2023
DOI: 10.3390/jcm12196303
|View full text |Cite
|
Sign up to set email alerts
|

The Predictors of Long COVID in Southeastern Italy

Vitaliano Nicola Quaranta,
Andrea Portacci,
Silvano Dragonieri
et al.

Abstract: Introduction: Long COVID is now recognized as a common consequence of the SARS-CoV-2 infection, but we are still far from fully understanding its pathogenesis and predictive factors. Many pathophysiological factors have been studied, including ethnicity. To our knowledge, the risk factors for Long COVID have not been studied in Southeastern Italy. Aims: The aim of this study was to evaluate the predictive factors of Long COVID in a cohort of patients from Southeastern Italy. Methods: We conducted a retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The incidence rate of LCS resulted in being different among cohorts due to study population heterogeneity, different COVID-19 severities, and the multifactorial pathogenesis of LCS [26]. The frequency of persistent symptoms after a mild COVID-19 infection was lower, ranging from 10% to 35% [27], than the aforementioned prevalence described in the studies including mostly hospitalized COVID-19 patients [23,24]. Indeed, our prevalence of LCS was similar to that observed in outpatients with mild COVID-19.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The incidence rate of LCS resulted in being different among cohorts due to study population heterogeneity, different COVID-19 severities, and the multifactorial pathogenesis of LCS [26]. The frequency of persistent symptoms after a mild COVID-19 infection was lower, ranging from 10% to 35% [27], than the aforementioned prevalence described in the studies including mostly hospitalized COVID-19 patients [23,24]. Indeed, our prevalence of LCS was similar to that observed in outpatients with mild COVID-19.…”
Section: Discussionsupporting
confidence: 67%
“…In the literature, the prevalence of LCS in adults was higher than in children. In a recent retrospective longitudinal study, including 436 Italian adult inpatients and outpatients previously diagnosed with COVID-19, the authors found LCS in 71.8% of patients [23]. Similarly, in a cohort of 1655 adults, LCS developed in 76% of subjects 6 months after hospitalization for COVID-19 [24].…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies, including those conducted in low-and middle-income countries, have established a link between female gender and long COVID ( 12 , 13 , 21 23 ), However, it has not been previously reported that a positive depression screening at day 30 using a validated questionnaire could be a risk factor for diagnosing long COVID at day 90 ( 24 , 25 ). Additionally, few studies have examined depression as a risk factor for COVID-19 or long COVID ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, a study from Southeastern Italy also demonstrated that corticosteroid therapy administered in the acute phase of COVID-19 might be associated with an increased risk of long COVID. One plausible hypothesis posited by the authors is that the administration of corticosteroids during the acute phase of illness may potentially contribute to the persistence of the virus within non-respiratory system among some patients reservoirs ( 24 ). To ascertain the potential association between corticosteroid utilization and an increased risk of prolonged COVID-19, along with its dependence on factors such as dosage, type, or duration of in-hospital steroid therapy, further comprehensive investigations are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…However, serum biomarkers were comparable between hospitalized and home‐isolated patients, with the unique exception of L‐selectin. This discrepancy might be explained, at least in part, with pharmacological interventions used during the acute infection, that could either increase (in particular corticosteroid therapy 32 ) or decrease (antiviral agents 33 ) the risk of long COVID. The low number of hospitalized subjects without long COVID symptoms and the heterogeneous type and dosage of medications used to manage the infection did not allow, in the present series, to adequately evaluate if the therapeutic approach to the acute event plays a role in the onset of long COVID.…”
Section: Discussionmentioning
confidence: 99%